Plano de renaturalização de trechos de canais urbanos de Belém-Pará-Brasil: contribuições para o planejamento urbano sustentável, e para o tratamento das inundações urbanas - SOARES, André Araújo Sombra (Servicios Académicos Intercontinentales S.L., 2021)
The present study presents the potential of sustainable urban planning entitled: "renaturation" of channels, in order to contain the problem of urban floods. And proposes the application of this planning to the city of Belém-PA, Brazil. It uses as a methodological procedure the literature review on the concept of renaturation, and the mapping of the Belém channels through geoprocessing. The result of this study is the finding that the city of Belém presents a number of sections of urban channels that are feasible for the implementation of the renaturalization plan.